"Against Right and Reason": The Bold but Smooth French Take-Over of Dutch Cayenne (1655–1664). Issue 1 (April 2021) - van den Bel, Martijn
Abstract: The Dutch loss of Brazil in 1654 favoured the resettlement of Dutch merchants along the Wild Coast and in the Lesser Antilles and the establishment of new colonies. Cayenne Island was one of them. One WIC patent was handed to Jan Claes Langedijck, who settled at the former French fort of Cépérou, and another patent was given to David Nassy, who settled in the Anse de Rémire, situated at the opposite part of the former island. Both colonies were taken by the French in May 1664 as part of the imperial French expansion under King Louis XIV and Jean-Baptist Colbert. It is argued here that the main French goal was to gain control of the sugar plantations of the Sephardic community located there, and, to a lesser extent, the much-desired territorial control of this region as proposed by the newly established French West India Company. The Dutch were aware of the attack, but could not intervene as it was already too late to send support to the poorly defended Cayenne colony. Both parties negotiated the take-over and the majority of the Dutch settlers stayed under French rule, as was suggested by the Dutch government and hoped for by the French.